THE EFFECT OF KOH AND SURFACE TREATMENT WITH TRIMETHYLSILYLCHLORIDE (TMSCL) AND POLYANILINE (PANI) IN SYNTHETIZING OF POROUS SILICON (PSI) - SYARIÃ‚Â’ATI (NIM : 10508058); Pembimbing : Dr. Veinardi Suendo, ALI
Since the accidental invention by Uhlir in 1956, the interest in porous silicon (pSi) continues to grow by looking at the number of publications until the late 90's. This interest is because of the unique properties and wide functions of pSi that can be used in various applications such as photovoltaic devices, gas sensors, drug delivery, and laser. pSi is synthesized electrochemically in HF solution at certain concentration. Electrochemical anodizing will result a sponge structure on the surface of pSi. Due to its small size or quantum confinement effect, the probability of radiative recombination in pSi increased significantly that leads to a room temperature photoluminescence. Photoluminescence tend to be unstable due to oxidation by air. The objective of the research is to determine the effect of potassium hydroxide (KOH) in the synthesis, and trimethylsilylchloride (TMSCl) and polyaniline (PANI) in the surface passivation related to the efficiency PL in pSi. The results of fluorescence measurements show that the effect of KOH on the PL intensity is more pronounced in the case where the mol of KOH is equivalent with HF in electrolyte solution. Morover, the surface treatment using TMSCl give the best result from the point of view of PL intensity. The morphology of pSi surfaces was observed using Scanning Electron Microscope (SEM).